ANALYSIS OF FIXED ASSET MANAGEMENT BASED ON THE MINISTRY OF HOME AFFAIRS REGULATION NUMBER 19 OF 2016 IN PAREPARE CITY - Andi Hikmah; Akhsan Akhsan (Journal AK-99, 2022)
This study aims to determine the management of fixed assets in Parepare City based on Ministry of Home Affairs Regulation Number 19 of 2016. It is hoped that the results of this study can become a source of reference for further researchers as well as information for the Government of ParepareCity. The data collection techniques used are documentation, observation, interviews, literature study and internet media with data sources was personal paper and place. The analytical technique used is descriptive qualitative analysis. The results of the study showed that in the management of regional property in the Badan Keuangan Daerah in Parepare City, it refers to the Ministry of Home Affairs Regulation Number 19 of 2016 about the management of regional property. Management of regional property at Badan Keuangan Daerah in Parepare City is carried out starting from planning, procurement, use, utilization, security and maintenance, appraisal, transfer, destruction, write-off, administration as well as supervision and control as stated in the Ministry of Home Affairs Regulation Number 19 of 2016. The inhibiting factor in the capital expenditures managementis the uneven quality of human resources, so that there are still human resources who have not dominate the guidelines for managing the regional property.